Meta analysis of indocyanine green fluorescence in patients undergoing laparoscopic colorectal cancer surgery - Deng, Jia; Hu, Wenting; Li, Yang; Xiong, Kai; Yue, Tinghui; Lai, Xiangquan; Xiao, Tianbao (Frontiers in Oncology, 2022)
This meta-analysis intended to systematically evaluate the clinical implications of indocyanine green fluorescence (ICG) in patients undergoing laparoscopic colorectal surgery. PubMed, MEDLINE, Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Medical Information System and China Biomedical Database were synthetically searched for studies published from inception to April 14, 2022. The randomized controlled trials comparing ICG-use with controls were selected. The incidence of anastomotic leakage (AL), lymph node detection, operation duration, intraoperative bleeding, postoperative morbidity, and hospitalization time were evaluated in summary analysis, and calculated the corresponding 95 % confidence intervals (CI). Subsequently, in addition to subgroup analyses, studies for heterogeneity, sensitivity, and publication bias were carried out. Consequently, 3453 patients in the enrolled 15 studies were included; 1616 patients were allocated to the experimental group, and 1837 patients were assigned to the control group. The ICG group had a significantly decreased risk of AL (RR: 0.50, 95% CI: 0.37–0.67) and shorter hospitalization time (SMD: -0.31, 95% CI: -0.54–-0.08) compared to the control group. Meanwhile, the ICG showed clearly better lymph node detection (SMD: 0.19, 95% CI: 0.02–0.36). However, when the content of operation duration (SMD: -0.07, 95% CI: -0.30–0.15) and intraoperative bleeding (SMD: -0.16, 95% CI: -0.35–0.04) were compared, no statistical significance was found. Furthermore, the pooled analysis of postoperative morbidity was not statistically significant (RR:0.79, 95% CI: 0.58–1.08). The results of the subgroup analysis of AL indicated that there may be regional variations in AL (RR: 0.50, 95% CI: 0.37–0.67) but not in postoperative morbidity (RR: 0.79, 95% CI: 0.58–1.08). In conclusion, the application of ICG in laparoscopic colorectal surgery can effectively reduce the AL, lymph node detection, and hospitalization time. However, more multicenter large-sample randomized controlled trials are required to further confirm its advantages. The meta-analysis was registered in PROSPERO (no. CRD42022288054).